Calorimetry of amorphous calcium carbonate is correlated with its lithification and durability as synthetic stone—implications for CO2 storage and utilization - Levey, Catherine; Reed, Jillian; Sanchez, Christopher; Schneider, Jacob; Constantz, Brent R. (Frontiers in Materials, 2024)
The properties of amorphous calcium carbonate (ACC) and its transformations to crystalline polymorphs are frequently studied in aqueous systems and in small quantities. In this work, synthetic calcium carbonate stones are created from bulk ACC and crystalline polymorphs synthesized from gaseous CO2 at a gradient of end pH. Some of the ACC's lithify into stones that are durable against an abrasion and impact test, while some of the ACC's create fragile, friable stones. When these ACC's which transform to durable stones and ACC's which transform into fragile stones are studied in calorimetry, significant differences are observed. These stones, synthesized from gaseous CO2, can be used as a storage reservoir for utilized CO2 in construction and other infrastructure applications.